Hermenéutica del habitar: El problema del desarraigo en Heidegger - Márquez Osuna, Francisco (2021)
Heidegger dictated "Bauen, wohnen, denken" to reflect on uprooting (Heimatlosigkeit). This concept serves to think about the positioning of the human, as mortals, before the loss of orientation exposed by the concealment of the divine, the exploitation of the earth and the contamination of the skies. In this sense, only in the face of loss, insecurity and discomfort, is that the human is led to question his own dwelling. On the other hand, the poetic dwelling found in the dream reality is also discussed at the same time as the concept of χώρα present in the Platonic dialogue of the Timaeus.